HEALTH LIFESTYLE "SEHATI" AMONG ELDERLY IN JAMBANGAN NURSING HOME SURABAYA - Lono Wijayanti; Yurike Septianingrum (Community Service Journal of Indonesia, 2021)
Getting older means increasing health problems faced. The degenerative process in the elderly causes a decrease in physical, psychological and social conditions. Hypertension is a disease that has a very close relationship with the elderly. The purpose of this community service activity is to increase knowledge about the importance of a healthy lifestyle called SEHATI (Sehat Tanpa Hipertensi) among the elderly at the Jambangan nursing home Surabaya. This community service was held on July 8, 2020 at the Jambangan Nursing Home in Surabaya, which was attended by 56 elderly people. The method used is through counseling and blood pressure checks. Counseling uses lecture and question and answer methods. Most of the elderly are female (73.2%), most (73.2%) are aged 60-74 years, almost half (42.9%) have first-degree hypertension (140-159/90-99mmHg). Before counseling as many as 14% of the elderly knew about hypertension and how to prevent it, and after this activity as many as 88% of the elderly experienced an increase in knowledge. Providing education can improve a healthy lifestyle, so that people are more aware of the importance of a healthy lifestyle so that blood pressure can be controlled properly.